Greek-Turkish Relations in the Post-Cold War Era. Implications of the American Response - Coufoudakis, Van (Études helléniques / Hellenic Studies, 1996)
Rather than reviewing the known issues that currently make up the agenda of Greco-Turkish relations, I propose to examine the implications of the American response to the issues affecting Greco-Turkish relations in the post-cold war era and how these issues may be resolved. The analysis that follows is not an attempt to shift the burden for the peaceful resolution of problems in Greco-Turkish relations to an external actor such as the United States, or to blame third parties for the lack of resolution of these problems. It is an affirmation, however, that Cold War policies and assumptionsplayed a pivotal role in the definition and conduct of Greek, Turkish and American policy in the region and that American policy has been the most significant external influence in the bilateral relations of Greece and Turkey. Greco-Turkish relations have deteriorated since the end of the Cold War because Turkey has capitalized on the conditions of the new international environment in order to promote its revisionist objectives in the region. Washington, by fostering Turkey’s ambitious role in the Balkans, in Central Asia and in the Middle East has encouraged Turkey’s revisionist objectives in the Aegean and in Cyprus.